Analysis of Microbial Molecular Ecology Techniques in Constructed Rapid Infiltration System - 姜昕 马鸣超 李俊 鲁安怀 钟佐燊 (Journal of earth science (Wuhan, China), 2011)
The microbial molecular ecology techniques, which were developed on the basis of molecular, were applied in studying the bacteria in Constructed Rapid Infiltration （CRI） system. These techniques are very efficient in better describing the bacterial diversity, microbial community distribution, and relations between microbial group structure and nitrogen contamination through the analysis of microbial nucleic acid sequence fragment in CRI. The results further revealed the removal mechanism of contamination, which is essential for the improvement of wastewater treatment in CRI.